Development of Learning Media in Adultery Materials as a Moral Provision for Generation Z - Fitri Umardiyah; Umdatul Aulia (SCHOOLAR: Social and Literature Study in Education, 2022)
This study aims to develop a video learning media on adultery that is valid and practical. This research is a research and development using the ADDIE Method (Analysis, Design, Development, Implementation, and Evaluation). The analysis technique of this study uses quantitative data in the form of scores from the validator, the value of the teacher's response, the value of student responses to video learning media in the form of questionnaire scores. Qualitative data in the form of interviews with education practitioners or fiqh teachers and criticism suggestions from validators. The results of this study produced a product in the form of a learning video. The feasibility of the product was obtained based on the results of the validation test and practicality test. Assessment by media experts got a score of 84% with a very valid classification or very feasible to use. Assessment by material experts got a score of 98% with a very valid or feasible classification. The results of the teacher's response questionnaire got a score of 90% with a very valid classification or very feasible to use. The results of the student response questionnaire got a score of 89.2% with a very practical classification. Based on these results, it can be concluded that video learning media is feasible to use.